2011
DOI: 10.1111/j.1743-6109.2011.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Clitoris, Vagina, and Cervix Mapped on the Sensory Cortex: fMRI Evidence

Abstract: Introduction-The projection of vagina, uterine cervix, and nipple to the sensory cortex in humans has not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
116
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(130 citation statements)
references
References 26 publications
13
116
1
Order By: Relevance
“…41 Indeed, the genital sensory cortex, identified in the classical Penfield homunculus, is located in the paracentral lobule. 42 These previous findings confirm that the activity of brain regions associated with rs72993629 plays a key role in sexual behaviours. However, further brain imaging studies with larger samples and CaD information are needed to confirm and deepen our understanding of the role of the variant identified in the CaD-RSB interplay.…”
Section: Discussionsupporting
confidence: 77%
“…41 Indeed, the genital sensory cortex, identified in the classical Penfield homunculus, is located in the paracentral lobule. 42 These previous findings confirm that the activity of brain regions associated with rs72993629 plays a key role in sexual behaviours. However, further brain imaging studies with larger samples and CaD information are needed to confirm and deepen our understanding of the role of the variant identified in the CaD-RSB interplay.…”
Section: Discussionsupporting
confidence: 77%
“…Komisaruk's team, who have been doing fMRI studies during female orgasm, recently found heightened activation in the prefrontal cortex (PFC) during female climax -something not seen in the previous studies of female orgasm (Komisaruk, 2004(Komisaruk, , 2005(Komisaruk, , 2011. Surprisingly, this was also the case in the individuals who can achieve orgasm by thought alone, a recently defined case of 'brain orgasms'.…”
Section: Resultsmentioning
confidence: 70%
“…No fMRI or other studies on the correlation of orgasm related mood changes and brain activation/deactivation have been reported yet. Komisaruk et al, reported that clitoral, vaginal and cervical stimulation differentially activated the regions of the sensory cortex (Komisaruk, 2011). Komisaruk & Whipple also reported some orgasms of none-genital origin, coining the term "brain orgasms", where there was no genital stimulation, orgasm might occur in some women (Komisaruk, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is problematic to equate simple intensity and satisfaction. Self-report studies consistently show predictable differences between orgasms on the basis of stimulation site, which is consistent with the objective physiological differences between vaginal, cervical and clitoral stimulation (Komisaruk, Beyers-Flores, & Whipple, 2006;Komisaruk & Whipple, 1995;Komisaruk et al, 2004Komisaruk et al, , 2011. It is surprising that Prause argues against self-report studies, given that her proposals are almost exclusively based on self-reports.…”
mentioning
confidence: 86%
“…Studies reveal that vagina and clitoris activate distinct afferent pathways (Komisaruk, Beyers-Flores, & Whipple, 2006;Komisaruk et al, 2004) and that stimulation of clitoris, vagina and cervix activate different regions of the brain's sensory cortex (Komisaruk et al, 2011). Such cortical differences are likely due to distinct afferents: sensory information from the clitoris to the brain is transmitted mainly by the pudendal nerve, whereas vaginal and cervical sensation is additionally conducted by the pelvic, hypogastric and vagus nerves (Komisaruk et al, 2004(Komisaruk et al, , 2006.…”
Section: Anatomical and Physiological Differences Between Vagina Cermentioning
confidence: 99%